The transfer of movables in the international commercial context – a comparison of German and South African law - Lengyel, Martin (University of Johannesburg, 2014)
L.LM. (International Commercial Law) Please refer to full text to view abstract
Keywords: Contracts (International law); Germany; International Commercial Law; Law of property; Property; South Africa

Proposal for a regulation on a common European sales law - Ciceri, Eliane (LUISS Guido Carli, 2014)
Historical development. Five W of CESL. Common European sales law.

The strategic importance of regional economic integration to multinational companies (MNCs) : a study of South African MNCs' operations in the SADC - Egu, Mathew Eleojo (University of South Africa, 2014)
Though the strategic importance of regional economic integration to multinational companies (MNC) has been researched extensively internationally, this concept has not been studied in South Africa. In fact, there is a growing nostalgia that with the South African Development Community (SADC) moving towards its set macroeconomic convergence targets; regional economic integration eventually leads to macroeconomic stabilisation. This ultimately becomes the root of growth in a region that has been severely affected by globalisation, financial crises, increasing government debt and budget deficit problems. This study, hence, tries to find out how the critical decisions of South African MNCs are made when operating within regional markets. Consequently, statistical econometric models were developed to test time-series data from 1980-2011 using the best (most efficient) linear unbiased estimator (BLUE) ordinary least square regression technique. An analysis was then done to investigate how South African firms have been able to gain maximum benefits by adopting the SADC as its major trading bloc in Africa. The study’s findings showed that the major barriers that impede MNCs of South African origin from penetrating these markets were custom duties, direct and indirect tariffs. It was observed that this would only be reduced by regional integration. Determined to critically interrogate the problems detailed in this research, three hypotheses were tested, analysed and subsequent interpretation of the findings revealed that South African MNCs contribute positively to regional economic growth and investment in the SADC. Furthermore, the study found out that although these factors were important, they were not the only variables that stimulated the competitiveness of South African MNCs in the SADC region. The literature review sections of this study found that the adoption of strategic management initiatives by MNCs improved the operation of transnational companies in South Africa. A comparison between the value of South African MNCs, as well as, other explanatory variables, and the Gross Domestic Product (GDP) of both South Africa and the SADC using time series data for the period 1980-2011 indicated that there was a positive relationship between the contribution of MNCs to South Africa’s economy and the GDP of both South Africa and the SADC. This proved that there is a significant link between MNC growth and national/regional productivity. In conclusion, the study established that the findings of the literature review were theoretically in sync with the empirical analysis. Also, the outcome of this study concurred with the findings of similar research. In essence, regional trade arrangements are an increasingly important element of the global trade environment, of which the move by South Africa’s MNCs to operate in the SADC market was a positive one. Finally, the study found out that for these firms to be successful in the international business arena, business management decisions need to be made, only after a detailed strategic analysis of the significance of regional economic integration is considered. This integrative framework certainly determines the operational efficiency, survival and profitability of most MNCs that operate within the region.
Keywords: FDI; Foreign direct investment; Macroeconomic convergence; Macroeconomic stability; Mergers & acquisitions; Multinational companies; Regional Economic Community; Regional Trade Agreements (RTAs); SADC; South Africa Development Community; Strategic management

The compatibility of Australian and South African private international law with the Hague Principles on Choice of Law in International Commercial Contracts - Adams, Faadhil (University of Johannesburg, 2014)
In 2006 the governing body of the Hague Conference on Private International Law furnished the Secretariat with a mandate to conduct a series of feasibility studies on the development of an instrument, relating to the choice of law in international contracts. The outcome of these studies was largely successful, finding that there was a need for an instrument of this nature and additionally it would be welcomed by the international legal community. In 2009 the Permanent Bureau of the Hague Conference on Private International Law was invited to form a Working Group (WG) to draft a soft-law instrument affirming party autonomy in international contracts on an international level. The Hague Principles on Choice of Law in International Commercial Contracts (P) was, thus, born. The P were drafted by a panel of experts representing the majority of the world’s legal systems. The working group commentary (WGC will be used to refer to the commentary, whilst WG will be used to refer to refer to the working group itself) which provided the discussions in respect of, and the reasoning behind, the principles has been invaluable in writing this dissertation. The purpose of this dissertation is to investigate the compatibility of Australian and South African law with the P. One of the aims of the P mentioned specifically in the preamble is that these principles are to be used by countries as a model with which to develop their own rules of private international law. A study of the current law as it stands in comparison to the P marks the first step in this exercise, through finding where the law differs we can begin to bridge the disparity between a specific country’s legal system and that of the P. Should the P become an important part of the private international law discourse comparative studies such as this will become common-place. The fact that the principles were drafted as a soft-law instrument is in line with the growing world trend. The flexibility that is achieved through the use of a soft-law instrument may lead to greater legal certainty down the road as contracting parties and international lawyers alike become more familiar with the principles. This familiarity may lead to consensus among experts from around the world and eventually invite the prospect of a binding instrument being drafted
Keywords: Australia; Conflict of laws; Contracts; Contracts (International law); South Africa

Addressing the legal issues of an innovative start-up company - Samoylov, Vlad (Victoria University of Wellington, 2014)
Before examining the substance of the law it is necessary to discuss the contrast between law and practice. It is important to keep in mind that the letter of the law is sometimes not what is done in practice. This realisation is often referred to as the “law and society perspective.” Advocates of this perspective treat legal doctrine as more than just a closed system because they recognise that there are other external influences at play. Beyond the law, people are also influenced by other factors such as social roles, morals, religion and culture. For example, university researchers have an external incentive mechanism outside of IP law. Such researchers frequently prefer to publish their results and discoveries in academic journals rather than file for patents. A patent cannot be granted where there has been a publication. However the researchers are motivated by other incentives such as access to research funds and the attainment of professorship. The Law and Society perspective highlights the fact that the formal processes, which are provided for by the law are at times substituted by informal customs and understandings. An information technology (IT) firm that contributed to this paper by participating in an interview (Interviewee A), provided a good example of such an occurrence. Rather than use any of the formal IP modes of protection which are discussed in the following sections of this paper, ‘Interviewee A’ uses a very unorthodox strategy to protect their IP. They said: “we rely on employment contracts, code of conduct, and especially personal ethics and behaviour to protect our IP. We therefore have a company culture that encourages teamwork and cooperation”.
Keywords: Intellectual property; Product safety standards

Mediation advocacy - Shaw, Annabel (Victoria University of Wellington, 2014)
Mediation has been a part of New Zealand’s employment statutory framework in one form or another for over a century, and has been the first port of call for employment disputes under the current Employment Relations Act for nearly 15 years.¹ I have been working as a mediator in this context for almost seven years in more than 1,000 mediations. Lawyers are playing a significant part in the field of mediation, with a large number representing clients in this forum on a regular basis. In an evaluation of 100 of my mediations over a ten-month period, 85% of parties were legally represented. This rate is consistent with anecdotal reporting across the employment mediation service. Lawyer representation in mediation is not unique to the employment context. There are various mediation schemes provided for under many New Zealand statutes as well as a wide raft of non-statutory mediation occurring in numerous settings. In my experience as a mediator with human rights and leaky building mediations, as well as working as a lawyer in a large commercial law firm, I am aware lawyers are representing clients in many other areas of mediation as well. Although there is a significant amount of mediation occurring and a large number of lawyers regularly appearing in mediation, my experience is that the majority of lawyers act in mediation as if they were in litigation and take an adversarial approach. My thesis is that lawyers have not adapted effectively to mediation and taken on the role of mediation advocacy. This paper explores the topic by first describing, in Part II, what I observe as lawyers’ adversarial approach in mediation. It then looks at other research to assess whether this experience is reflective of a wider issue. It finds there is evidence to support my observations. Part III analyses why lawyers are operating in an adversarial way in mediation and proposes several reasons this may be the case. Part IV puts forward what I propose is appropriate mediation advocacy. It sets out the knowledge, roles and skills required from lawyers when representing clients in mediation. Part V suggests what might be done to assist a shift away from the common, adversarial approach to effective mediation advocacy. This paper is written within the context of employment mediation in New Zealand. However, it draws on research from different jurisdictions and areas of practice so the conclusions it comes to may have more general application. The topic is not whether lawyers should be in mediation. I am not arguing that lawyers do not have a part to play in mediation. A lawyer well versed in mediation advocacy can play a highly effective part in the process. Leonard Riskin, one of the key authors on the topic of lawyers in mediation, expresses this even more strongly, saying he believes lawyers’ involvement is fundamental to mediation’s success.² Further, this paper is focused on lawyers representing parties in mediation and does not consider lawyers as mediators.
Keywords: Advocacy; Dispute resolution; Employment disputes; Lawyers; Mediation

Sanitary and phytosanitary measures in the SADC region : a South African legal perspective - Joubert, Biandri (North-West University, 2014)
Sanitary and phytosanitary (SPS) measures are measures aimed at the protection of human, animal and plant life and health within specified territories from the risks associated with the introduction and spread of pests and diseases through trade. The World Trade Organisation (WTO) developed an agreement on the application of SPS measures. South Africa is a member of both the WTO and the Southern African Development Community (SADC). In SADC, SPS measures are provided for in the SADC Sanitary and Phytosanitary Annexure to the Protocol on Trade of 1996. International Standard Setting Bodies (ISSBs) facilitate the effective application of the main elements of the relevant SPS agreements, especially harmonization and equivalence by establishing scientifically justified standards on which members may base their SPS measures. The relevant ISSB’s in terms of SPS measures are the OIE, IPPC and Codex Alimentarius. SPS measures have the potential to become or be used as non-tariff barriers to trade (NTBs). The SADC Protocol on Trade 1996 stipulates that policies and measures are to be implemented by members to eliminate existing forms of NTBs. Additionally members may not enforce new NTBs affecting or related to intra-SADC trade. The most relevant South African legislation in the context of SPS measures and this study is as follows: Agricultural Pests Act 36 of 1983, the Agricultural Products Act 119 of 1990; the Fertilizers, Farm Feeds, Agricultural Remedies and Stock Remedies Act 36 of 1947, the Liquor Products Act 60 of 1989, Meat Safety Act 40 of 2000, Foodstuffs, Cosmetics and Disinfectants Act 54 of 1972, Medicines and Related Substances Act 101 of 1965 and National Regulator for Compulsory Specifications Act 5 of 2008. The purpose of this study is to establish to what extent the South African legal framework complies with its obligations in terms of the SADC SPS Annexure to the Protocol on Trade.
Keywords: ISSB; NTB; SADC; SPS; Sanitary and phytosanitary measures; South Africa; WTO

A critical assessment of the impact of SPS measures on market access for developing countries : case study of South Africa and Kenya - Mupure, Ngonidzashe L. A. (University of KwaZulu-Natal, 2014)
Abstract not available.
Keywords: Developing countries; Economic conditions; Economic development; International Trade; Kenya; Phytosanitation; South Africa

A critical discussion on foreign direct investment in the multilateral trade system and development in SADC - Nhlakanipho, Macmillan Zikalala (University of KwaZulu-Natal, 2014)
Development is understood to be an economic process that aims at a constant improvement of the well-being of all individuals who have the right to participate and benefits from the fruits of development. Development is also a right that requires a progressive realisation by governments, international communities and private sectors to the satisfaction of all individuals. A progressive realisation of this right requires a vibrant economy, which can be acquired through International trade and Foreign Direct Investment (FDI). It is in this context that this thesis has attempted to discuss the influence of FDI and International trade on development. The discussion was initiated by focusing on the history of the multilateral trade system (MTS) by looking at various Ministerial rounds of both the General Agreement on Tariffs and Trade (GATT) and the World Trade Organisation (WTO). In this discussion the thesis found that, whilst there are various multilateral political frameworks regulating trade, FDI is subject to regional and domestic political frameworks. The thesis also discussed development in relation to the millennium development goals (MGDs). It was established the goal eight of the MDGs requires the integration of poor countries into the MTS so that they can be able to exploit their comparative advantage. This goal influenced the launching of the Doha Development Agenda (DDA) at the Doha round in 2001. However, the thesis also established that conclusion of the DDA has been progressing at a slow pace. Therefore it has not yielded substantial results for poor countries. The failure to conclude the DDA has led to an increase of Regional Trade Agreements (RTAs), which some scholars view as a supplement of multilateral trade integration. However, the SADC region has not been able to conclude their integration objectives due to the fact that many member states belong to other RTAs. In the case of FDI the thesis established that FDI is accompanied by a wide range of resources for host countries, which can be utilised for enhancing development. However, it was also established that the SADC has not been able to attract lucrative FDI due to a wide range of factors that impede FDI. On this finding, a case study was employed on four countries in the region, namely Angola, Botswana, South Africa and Zimbabwe.
Keywords: Economic Policy; FDI; Foreign direct investment; International Trade; International economic relations; Investments

Copyright and developing countries a critical examination of recent developments in copyright law with particular reference to the impact on developing countries and access to educational materials - Siphepho, Nomvuyo Nicole (University of KwaZulu-Natal, 2014)
Abstract not available.
Keywords: Copying processes; Copyright; Developing countries; Instructional materials industry